Manajemen jasa logistik pelayaran redpack guna mengurangi waste: studi kasus PT. PELNI - Moses Laksono Singgih; Rizka Safira Hartanti (Universitas Mercu Buana, 2020)
PT. PELNI is a company that provides shipping services using sea transportation. One of the services it has is REDPACK, which is a delivery service with priority to maintain package conditions. This service is still relatively new because it is operating in 2019 and evaluation is needed so that efficiency increases by reducing waste. In this study, the method used is Lean Service because the delivery service is in the service sector. The tools used in this research are Value Stream Mapping (VSM) and DEMATEL. VSM is used to analyze the value flow in the service process. VSM results can indicate a process that is not needed. After that, it is continued by identifying process flow waste and determining critical waste in these services. Determination of critical waste is done using DEMATEL. DEMATEL is a method used to analyze the cause-effect relationship of a complex system. The results showed that the main waste factor in logistics services is customer activity reporting incoming cargo. This waste can be repaired by moving the office location into one room with a new warehouse and activity flow.